Determination of appropriate brand strategy under its price category - N.E. Kosolap; T.О. Bashuk (Marketing i Menedžment Innovacij, 2011)
This article analyzes the components of the concept of brand, focused on the study of price orientation Ukrainian brands, suggested strategies for companies with different market shares according to their price positioning.